Assessing data quality of remotely-sensed DEM’s in hungarian sample area - Szabó, Gergely; Mecser, Nikoletta; Karika, Anita (Acta Geographica Debrecina Landscape & Environment series, 2013)
Nowadays the free-access digital elevation models are getting more and more popular. The SRTM and ASTER GDEM databases are the most widespread. However, there are numerous situations and weaknesses we have to take into account during their usage, such as direction-dependent accuracy and difference between digital and real surfaces. Our goal was to examine these kinds of deficiencies of surface models.